PENGARUH SPEED READING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA MATA PELAJARAN BAHASA INDONESIA SD NEGERI 55 PAREPARE - muhammad asrul sultan; Nilawati Nur (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This objective of this research was to determine the effect of speed reading on students reading comprehension on subjects Bahasa Indonesia in SD Negeri 55 Parepare. This research was Quasy Experimental Design with the form of none equivalent control group design. The sampling technique used was nonprobability with a type of purposive sampling technique and the samples was 50 students, they were the experiment group dan control group. The data collection technique used was a mupltiple choice test and documentation. Data analysis used descriptive statistical analysis techniques and inferential statistical analysis techniques. The results of this research  is that speed reading can have a positive influence on improving students reading comprehension on subjects Bahasa Indonesia in class V SD Negeri 55 Parepare.